Pengaruh procedural justice terhadap work engagement melalui organizational trust dan organizational commitment sebagai variabel intervening - Nadziroh, Uyun; Nugrohoseno, Dwiarko (Jurnal Ilmu Manajemen, 2023)
This study aims to test and analyze the effect of procedural justice on work engagement through organizational trust and commitment as intervening variables. The approach used in this study is quantitative. The sampling technique uses a saturated sample of 90 employees in PT X. The data in this study were analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) with SmartPLS 4.0.9 software. The results showed that procedural justice has a positive effect on organizational trust and organizational commitment, procedural justice does not affect work engagement, organizational trust does not affect organizational commitment and work engagement, organizational commitment has a positive effect on work engagement, organizational trust does not mediate the relationship between procedural justice and work engagement, organizational commitment mediates the relationship between procedural justice and work engagement, organizational trust and organizational commitment does not mediate the relationship between procedural justice and work engagement. Companies must pay more attention to employee work engagement by increasing procedural justice and organizational commitment.